Effect of pouring temperature and cooling slope length on microstructure and mechanical properties of Rheocast A319 aluminium alloy - Salleh, Mohd Shukor; Omar, Mohd Zaidi; Syarif, Junaidi; Mohammed, Mohammed Naser; Alhawari, Khaled Salem (Trans Tech Publications, Switzerland, 2015)
Aluminium alloys are among the most prominent and well known materials used in automotive industries. Nowadays, many vehicles used aluminium engine blocks instead of cast iron to improve fuel efficiency. Among cast aluminium alloys, A319 grade alloys are normally used in automotive industries due to a combination of good fluidity and mechanical strength. In this study, A319 cooling slope rheocasting billets were produced in order to obtain near spherical morphology of primary aluminium phase. The change in the α-Al morphology upon the cooling slope casting was remarkable and the dendritic microstructure was almost replaced by α-Al globules and rosettes. The rheocasting billets were prepared for tensile testing at room temperature. It is found that, the yield strength and elongation of cooling slope rheocasting billets is higher than those from as-cast A319 alloy.